A Systematic Approach of Generalized Reactance Compensation Technique in Wideband Class-E Power Amplifier for Lower High Frequency (HF) Bands - Khairul Hilmi Yusof; Farid Zubir; Mohamad Kamal A. Rahim; Narendra Kumar; Zubaida Yusoff; Peter Gardner; Thomas Johnson (IEEE Access, 2023)
This paper discussed a systematic design approach for reactance compensated class-E power amplifier. The theory behind conventional Class-E is described then differences between reactance compensation Class-E is explained and derived. The reactance compensated Class-E gives better high efficiency bandwidth. The range of shunt capacitor value that can maintain high efficiency operation also increases compared to conventional Class-E. The overall impedance for reactance compensated Class-E is derived and shows that it is the same as Class-E. The contribution of this paper is to present a high-performance wideband Class-E Power Amplifier in the operating frequency of low MHz range for the first time. Also, a systematic design approach on the theoretical derivation of Class-E Power Amplifiers with reactance compensation method is presented in this work. To verify the design method and simulation results, we fabricated and measured the proposed design. Wideband Class-E Power Amplifier at low MHz frequency is achieved. The results show that all simulation, designing methods and experimental results confirm each other. The theoretical and simulated results of reactance compesnated Class-E shows 17.3% and 33.3% increase in high efficiency bandwidth compared to conventional Class-E. The measurement result shows the reactance compensation technique shows an increase in its high efficiency bandwidth by 52.3% compared to conventional Class-E. Reactance compensation can be used to improve the high efficiency bandwidth of conventional Class-E and shows promises in realizing wideband Class-E. As the overall impedance of reactance compensated Class-E is the same as conventional Class-E, implementing this method would simplify the analysis in other high efficiency amplifier topologies like push-pull, Doherty, and Outphasing